2003
DOI: 10.1074/jbc.m310865200
|View full text |Cite
|
Sign up to set email alerts
|

Metalloproteinase Expression in PMA-stimulated THP-1 Cells

Abstract: The PPAR␥ agonists, thiazolidinediones (TZDs), have anti-inflammatory properties as well as increasing insulin sensitivity. This has widened their therapeutic scope to treat inflammatory diseases such as atherosclerosis in addition to Type 2 Diabetes. TZDs are known to reduce monocyte/macrophage expression of Matrix metalloproteinase (MMP)-9, which is implicated in atherosclerotic plaque destabilization. This study aims to identify other metalloproteinase genes of the ADAM (A Disintegin And Metalloproteinase) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
23
0

Year Published

2004
2004
2015
2015

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 82 publications
(26 citation statements)
references
References 64 publications
3
23
0
Order By: Relevance
“…PPAR␥ agonists were also found to inhibit MMP3 expression in human rheumatoid fibroblast-like synoviocytes (44). Down-regulation of MMP9 by natural (15d-PGJ2) and synthetic (GW7845) PPAR-␥ ligands in PMA-stimulated THP-1 monocytes has been consistently observed (31). An inhibition of MMP13 expression by Rtz was also reported by Fahmi et al (3) in human chondrocytes.…”
Section: The Ppre Sequence Situated At ϫ83 To ϫ71 In the Mmp1 Promotesupporting
confidence: 59%
“…PPAR␥ agonists were also found to inhibit MMP3 expression in human rheumatoid fibroblast-like synoviocytes (44). Down-regulation of MMP9 by natural (15d-PGJ2) and synthetic (GW7845) PPAR-␥ ligands in PMA-stimulated THP-1 monocytes has been consistently observed (31). An inhibition of MMP13 expression by Rtz was also reported by Fahmi et al (3) in human chondrocytes.…”
Section: The Ppre Sequence Situated At ϫ83 To ϫ71 In the Mmp1 Promotesupporting
confidence: 59%
“…Thus, the IFN-induced downregulation of surface TACE seemed to likely occur via the internalization of TACE. Previous studies showed that PMA upregulated TACE transcripts in leukemic myeloid tamm-horsefall protein-1 (THP-1) cells (Worley et al, 2003) and downregulated surface TACE (Doedens and Black, 2000). This downregulation occurred via the internalization and degradation of TACE molecules (Doedens and Black, 2000).…”
Section: Ifns Affect Ace and Tace In Normal And Leukemic Myeloid Cellmentioning
confidence: 98%
“…Monocyte as well as monocyte-derived macrophage MMP-9 is tightly regulated at the transcriptional level by the transcription factor NF-κB 2,16 and rapidly increases in processes involved in vascular inflammation and atherogenesis. 11,53 However, the precise factors that stimulate MMP elaboration in lesion-associated macrophages have not been well characterized to date. 9 NF-κB is active in lesion-prone regions and NF-κB-regulated inflammatory responses play major roles in atherosclerotic lesion initiation and progression of atherogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…4 During all stages of atherogenesis, monocytes and macrophages secrete proteolytic enzymes, which may influence plaque composition or stability. 10,11 Migration of macrophages into atherosclerotic tissue as well as subsequent plaque remodeling and progression require the degradation of tissue matrix proteins by matrix metalloproteinases (MMPs) such as MMP-2 or MMP-9.…”
mentioning
confidence: 99%